Prognostic Value of Intratumor Metabolic Heterogeneity Parameters on 18F-FDG PET/CT for Patients with Colorectal Cancer. (30th January 2022) - Liu, Xin; Xiang, Kun; Geng, Guang-Yong; Wang, Shi-Cun; Ni, Ming; Zhang, Yi-Fan; Pan, Hai-Feng; Lv, Wei-Fu
Abstract : Purpose . Intratumor metabolic heterogeneity parameters on 18 F-2-fluoro-2-deoxy-D-glucose ( 18 F-FDG) positron emission tomography-computed tomography (PET-CT) have been proven to be predictors of the clinical prognosis of cancer patients. The study aimed to examine the correlation between 18 F-FDG PET-CT-defined heterogeneity parameters and the prognostic significance in patients with colorectal cancer. Methods . The study included 188 patients with colorectal cancer who received surgery and 18 F-FDG PET/CT examinations. Preoperative 18 F-FDG PET/CT conventional and metabolic heterogeneity parameters were collected, including maximum, peak, and mean standardized uptake value (SUVmax, SUVpeak, and SUVmean), metabolic tumor volume (MTV), total lesion glycolysis (TLG), heterogeneity index-1 (HI-1) and heterogeneity index-2 (HI-2), and clinicopathological information. Correlations between these parameters and patient survival outcomes were inferred. Results . The associations between 18 F-FDG PET/CT parameters and clinical outcomes were analyzed. Tumor thrombus (P < 0.001 ), tumor stage (P = 0.001 ), MTV (P = 0.003 ), HI-1 (P = 0.032 ), and HI-2 (P = 0.001 ) differed between the two groups with and without recurrence. Multivariate analysis showed that, in the radical surgery group, HI-2 (HR = 1.10, 95% CI: 1.04–1.17, P = 0.001 ), tumor stage (HR = 20.65, 95% CI: 4.81–88.62, P < 0.001 ), and regional lymph nodes status (HR = 0.16, 95% CI: 0.04–0.57, P = 0.005 ) were independent variables significantly correlated with progression-free survival (PFS) and HI-2 (HR = 1.16, 95% CI: 1.07–1.26, P < 0.001 ) was an independent variable affecting overall survival (OS). In the palliative surgery group, HI-2 (HR = 1.03, 95% CI: 1.01–1.06, P = 0.020 ) was an independent variable affecting PFS, and all the parameters were not statistically significant for OS. Conclusion . HI-2, tumor stage, and regional lymph nodes status might predict the outcomes of colorectal cancer more effectively than other 18 F-FDG PET/CT defined parameters.